From Corporate Governance To Corporate Social Responsibility In Malaysia : The Evolving Boardroom Agenda - Akmal Arief, Mohd Fauzi (2003)
With the changing expectation of business in the society, it is not surprising that Corporate Social Responsibility has gained more prominence in recent years along with emphasis for Corporate Governance. Company’s boards are now facing increased responsibility with regards to stakeholder relationship. Continued existence of companies is based on an implied agreement between business and society, where the essence of the contract between society and business is that companies shall not pursue their immediate profit objective at the expense of the longer term interests of the community. Conduct of corporations has all the while been regulated by Codes of Corporate Governance. A Friedmanite view of the firm whereby there is an emphasis on purely financial aspect of the business is no longer appropriate in a society, which is increasingly taking an inclusive view of the business. Many companies have responded to this more inclusive approach by starting to disclose and report not just the traditional financial performance of the company but “triple bottom line” which essentially encompass economic, social and environmental performance. The triple bottom line conveys a wider information set than financial information and helps to present a wider picture of company’s performance in relation to social and environmental matters. In contrast to Corporate Governance disclosure, which was made mandatory by the regulators, Malaysian companies are still “new” in reporting social and environmental performance. This study sets out to assess the state of Corporate Social Responsibility reporting in particular and the Corporate Social Responsibility in general, Malaysian context. This is done by documenting the findings of other previous studies as well as scrutinising the annual reports of a randomly selected public listed companies. The study then, moves further to provide explanations and trends as observed. Feedback were also obtained from interviews, especially on aspects of Corporate Governance and Corporate Social Responsibility in general. The result reveals that Corporate Governance disclosure is very much complied by Malaysian companies but further improvements can be undertaken. Companies are now governed more systematically with increased transparency/accountability. Corporate Social Responsibility reporting, voluntary it may be, are found to be practised by a majority of the sample companies. Disclosure themes range from Human Resource/Employee, Welfare/Community Services, and Environment all the way to Sports and Arts/Culture. The study also found that Corporate Social Responsibility in general has been widely practised by Malaysian companies especially the “philanthropic” aspects, not surprising considering the development stage, culture and society demands specific to the country. Nonetheless, the approach has been an integrated and comprehensive one with all “pillars” of economics, legal, ethical and philanthropic present. It is then further concluded that Corporate Social Responsibility goes hand in hand with Corporate Governance in improving conduct of businesses and providing a holistic “spirit”, thus, remains as the topmost priority of Malaysian public listed corporations’ boardroom agenda.